An experimental and numerical study on the translaminar fracture of cross-ply non-crimp fabric composites. (January 2023) - Gouskos, D.; Iannucci, L.
Abstract: In this paper, the damage propagation of a cross-ply Non-Crimp Fabric composite under Compact Tension is numerically modelled. The work includes an experimental study through which the internal structure of the composite is characterised, the translaminar fracture toughness values are obtained and the sequence of failure mechanisms are identified. Based on the experimental findings, a new exponential law is introduced during element failure under fibre tension to describe the unloading phase incorporating the fracture toughness as the governing parameter for material degradation. Furthermore, a power law based on the maximum strain criteria for transverse tension and in-plane shear loading is proposed to formulate the interactive damage propagation of the 90 o layers. A set of physically-based failure criteria at layer level which account for the induced in- and out-of-plane fibre misalignment is associated with an energy-based damage mechanics method and implemented in Abaqus/Explicit as a VUMAT subroutine. The load–displacement response at all stages as well as the evolution of the translaminar fracture toughness during damage propagation are compared successfully against the experimental results. Highlights: Fibre pull-out is the dominant failure mode for cross-ply NCF composites under CT. In-plane fibre misalignment is responsible for fibre splitting of the 0 o layers during CT. Excessive in- & out-of-plane fibre misalignment can result in undesired compressive failure at the rear end of a CT specimen. R-curves were over predicted with app. 5.8% against test results with the use of the exponential unloading law. The load and corresponding displacement at damage onset was overestimated by the constitutive model by app. 3.5% & 2.7% respectively. The exponential unloading law during element failure in fibre tension captured successfully the softening behaviour of the load response.